Effects of Using the Scratch Program in 6th Grade Information Technologies Courses on Algorithm Development and Problem Solving Skills - Oluk, Ali; Saltan, Fatih (Participatory Educational Research (Per), 2015)
This study aimed to identify the effects of using the scratch program in 6 th grade information technologies courses on algorithm development and problem solving skills. The study utilized pretest – posttest control group experimental design. A total of 65 (34 control, 31 experimental) 6 th grade students in a secondary school in Taskopru District of Kastamonu Province participated in the study. The study was designed quasi-experimentally. Algorithm Development Test and Problem Solving Inventory developed by Serin et. al. for primary grade students were used as pre and post tests.   Algorithm Development Test: Students were asked four open-ended questions to test their algorithm development skills. The questions aimed to identify skills related to algorithm development, flowchart development, explaining a given algorithm and detecting errors in a given algorithm. A researcher, an information technologies teacher and an instructor undertake the assessment of the Algorithm development test. The Algorithm Development Test score was obtained by taking the average of the three scores.  Control group students learned algorithm as presented in the curriculum whereas control group students learned algorithm with the help of the scratch program.  Implementation classes received 2-hour Information Technologies instruction per week. The implementation period covered a 6-week process. Results showed no significant differences between the control and experimental groups in terms of algorithm development skills and problem solving skills
Keywords: Eğitim Üzerine Çalışmalar; Scratch; programming education; problem solving skill; visual programming; Studies on Education; 4. Education; 3. Good health